Master Athletes Are Extending the Limits of Human Endurance - Lepers, Romuald; Stapley, Paul J. (Frontiers in Physiology, 2016)
The increased participation of master athletes (i.e. > 40 years old) in endurance and ultra-endurance events (> 6h duration) over the past few decades has been accompanied by an improvement in their performances at a much faster rate than their younger counterparts. Ageing does however result in a decrease in overall endurance performance. Such age-related declines in performance depend upon the modes of locomotion, event duration and gender of the participant. For example, smaller age-related declines in cycling performance than in running and swimming have been documented. The relative stability of gender differences observed across the ages suggests that the age-related declines in physiological function did not differ between males and females. Among the main physiological determinants of endurance performance, the maximal oxygen consumption (VO2max) appears to be the parameter that is most altered by age. Exercise economy and the exercise intensity at which a high fraction of VO2max can be sustained (i.e. lactate threshold), seem to decline to a lesser extent with advancing age. The ability to maintain a high exercise-training stimulus with advancing age is emerging as the single most important means of limiting the rate of decline in endurance performance. By constantly extending the limits of (ultra)-endurance, master athletes therefore represent an important insight into the ability of humans to maintain physical performance and physiological function with advancing age.